The Effectiveness Of The Application Of The Field Trip Method In Learning Arabic Language To Improve Writing Skills For Grade 8 At Madrasah Tsanawiyah Darul Faizin Mojowarno Jombang - Abidin, Hasan (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2022)
This study explains about "the effectiveness of the application of the Field Trip Method in Arabic Learning to Improve Writing Skills for Grade 8 at Madrasah Tsanawiyah Darul Faizin Mojowarno Jombang”. The choice of the title is based on the assumption that the FIELD TRIP method is a learning that involves the work of the left and right brain which will make learning for students light and fun because learning with this method is different from existing lessons, the learning is by inviting students towards an object outside the school that is not too far away to learn so that students do not experience boredom and stress in learning. By exposing the student to the real object, it is hoped that it can support the maharoh of the student's book. This research method in writing this scientific paper is qualitative and quantitative using the "t" test formulas to analyze the data, because this type of research is an experimental type of research. This study aims to determine the significance of differences in the level of achievement of students' maharoh kitabah before and after using the Field Trip method on 191 students consisting of 6 classes. While the sample used is simple random sampling, ie data collection is done because members of the population are considered homogeneous. The research sample was 39 students and data collection was done by observation, interviews, and tests. The results showed that there was a significant difference between the student's maharoh kitabah before and after using the Field Trip method, it can be seen from to stronger than tt 2.20 < 5,625 > 2.71. These results show that Ho is rejected and Ha is accepted. As a closing of the abstraction of this scientific work, the author suggests to Arabic language teachers to always develop their creativity to maximize the achievement of the objectives of the teaching and learning process.